Potentially serious adverse effects from application of a circumferential compression device for pelvic fracture: A report of three cases. (April 2020) - Suzuki, Takashi; Kurozumi, Taketo; Watanabe, Yoshinobu; Ito, Kaori; Tsunoyama, Taichiro; Sakamoto, Tetsuya
Abstract: Pelvic circumferential compression devices (PCCDs) have gained wide acceptance in the management of patients with pelvic fracture. These devices are considered safe due to their noninvasive nature and significant hazards associated with the use of PCCDs have not been reported previously. However, we present herein the cases of three patients who received PCCD application and eventually developed major complications presumably caused by PCCDs. As a result, one patient developed surgical site infection following internal fixation and required several debridements. Another patient ended up with a walking disability. The remaining patient eventually died from exsanguination following application of the PCCD. Clinicians should be aware of the potential for deleterious effects, including bladder rupture, muscle necrosis, and vessel injuries. In particular, application for acetabular fractures and prolonged application of PCCDs should be avoided.